Akt pathway activation reduces platelet apoptosis and contributes to the increase of platelet counts in solid tumor patients. (3rd October 2022) - Tian, Huan; Huang, Songyin; Luo, Qing; Lin, Zhuochen; Liu, Huanhuan; Zhang, Zhixian; Fong, Wengcheng; Zhao, Jinghua; Yu, Fengyan
Abstract: Platelets counts increase in various cancer patients, which is associated with poor prognosis. However, the cause of high platelet counts in cancer patients is still not fully understood. Here we demonstrated that compared with healthy controls, there were significant differences in platelet parameters, mean platelet volume (MPV), platelet distribution width (PDW), platelet larger cell ratio (P-LCR), and platelet crit (PCT), reflecting platelet volume in breast cancer patients by clinical retrospective analysis. The mitochondrial transmembrane potential (ΔΨm) depolarization and phosphatidylserine (PS) externalization declined, accompanied by reduced expression of pro-apoptotic factors Bak, Bax and apoptotic executor caspase-3, and elevated of anti-apoptotic factor Bcl-xl in various cancer patients' platelets. Notably, the phosphorylation level of Akt and its downstream target Bad increased in platelets from cancer patients. MK2206, the inhibitor of Akt, reduced the phosphorylation level of Akt and Bad, and induced apoptosis of platelets. When platelets from healthy controls cocultured with the cultural supernatant of cancer cells, the phosphorylation level of Akt and Bad in the platelets was elevated and the cultural supernatant of cancer cells could rescue the apoptosis of platelet induced by MK2206. Therefore, in our study the apoptosis of platelets in cancer patients was declined, which exerted an influence on the rise of platelet counts in breast cancer patients. The cross-talking between tumor and platelets could affect platelet apoptosis by regulating Akt signaling pathway in platelets.